Conflicting attitudes between clinicians and women regarding maternal requested caesarean section: a qualitative evidence synthesis - Margareta Johansson; Jonatan Alvan; Agneta Pettersson; Ingegerd Hildingsson (BMC, 2023)
Abstract Background Caesarean section (CS) can be a life-saving operation but might also negatively affect the health of both the woman and the baby. The aim of this study was to synthesize and contrast women's and clinicians' attitudes toward maternal-requested CS, and their experiences of the decision-making process around CS. Methods The databases of CINAHL, MEDLINE, PsycInfo and Scopus were screened. All qualitative studies that answered the study question and that were assessed to have minor or moderate methodological limitations were included. Synthesised findings were assessed using GRADE-CERQual. Results The Qualitative Evidence Synthesis included 14 qualitative studies (published 2000-2022), involving 242 women and 141 clinicians. From the women's perspectives, two themes arose: women regarded CS as the safest mode of birth; and women's rights to receive support and acceptance for a CS request. From the clinicians' perspectives, four themes emerged: clinicians were concerned about health risks associated with CS; demanding experience to consult women with a CS request; conflicting attitudes about women's rights to choose a CS; and the importance of respectful and constructive dialogue about birthing options. Conclusion Women and clinicians often had different perceptions regarding the right of a woman to choose CS, the risks associated with CS, and the kind of support that should be part of the decision-making process. While women expected to receive acceptance for their CS request, clinicians perceived that their role was to support the woman in the decision-making process through consultation and discussion. While clinicians thought it was important to show respect for a woman's birth preferences, they also felt the need to resist a woman's request for CS and encourage her to give birth vaginally due to the associated increases in health risks.